Modern aspects of treatment of hiatal hernia and its main complications - A. Yu. Usenko; O. S. Tyvonchuk; О. P. Dmytrenko; I. S. Tereshkevych; I. V. Babii (Zaporožskij Medicinskij Žurnal)
The aim. To evaluate the features and results of minimally invasive surgical treatment of patients with hiatal hernia (HH) and its main complications using modern endoscopic and laparoscopic technologies.